Democracy Making melalui Musyawarah Desa di Desa Bendungan Kecamatan Kaliwiro Wonosobo - Mohamad Firdaus (Jurnal Masyarakat dan Desa, 2022)
Democracy making through village deliberation is a deliberative theory of democracy to control and aggregation. Explorative Qualitative Research is used to explore phenomena and explore concepts related to making democracy in Bendungan Village. The data is analyzed by phenomena that occur in people's lives. Data collection was done by observation, documentation and interviews. The results of the study show that democracy making in Bendungan Village is carried out through village deliberations which are held twice a year which is the result of democracy making hamlet deliberations and non-formal deliberations such as Friday night tahlilan events, recitation and patrols. In these non-formal deliberations, political spaces are opened to discuss various kinds of community interests in order to become a means of control and aggregation. With strong deliberation at Friday night such as tahlilan events, women's recitations, night patrols, community service, and posyandu (Integrated Healthcare Center) which are carried out routinely, in addition to controlling power and aggregation, genuine people's aspirations can emerge that are autonomous and not based on mobilization based on community modalities